"If they have more work, they learn more": parents' views of their children's learning experiences and homework in Pre-K settings. Issue 3 (27th May 2022) - Liang, Eva; Peters, Lacey Elizabeth; Akaba, Sanae; Lomidze, Ana; Graves, Sherryl Browne
ABSTRACT: This study examined parents' perspectives on children's learning in Pre-K, their expectations for Pre-K, and how to prepare their child(ren) for kindergarten. Researchers conducted semi-structured interviews with 22 ethnically diverse parents from 8 schools in New York City. This paper presents a thematic analysis of these interviews. Findings revealed parents believed children's academic learning should be the focus for kindergarten readiness, with an emphasis on language and literacy and mathematics. They frequently mentioned homework as a hands-on activity that promotes children's learning. With the continued increase in funding and attention to Pre-K, there needs to be a greater understanding of how parents conceptualize kindergarten readiness and structure learning experiences for children, and how Pre-K curriculum is changing extended learning. Parents' views should be considered in decision-making around programming with regard to daily instruction, as well as facilitating the transition to elementary school.